Engineering Leadership in Multicultural Environments: A Review of Management Strategies and Outcomes - Hosseinzadeh, Seyed Mostafa (Management Strategies and Engineering Sciences, 2023)
Engineering leadership in multicultural environments presents unique challenges and opportunities, requiring leaders to navigate cultural differences, foster inclusive communication, and employ adaptable management strategies. This narrative review synthesizes the existing literature on leadership within multicultural engineering contexts, focusing on the management strategies that enhance team performance and project outcomes. The review highlights the importance of cultural intelligence, adaptability, and communication in managing diverse teams, with specific strategies like team-building and conflict resolution proving effective in different contexts. The findings suggest that while co-located teams benefit from direct interaction and team cohesion, geographically dispersed teams require enhanced communication technologies to bridge physical gaps. Despite the progress in this field, there remain significant gaps, particularly regarding the long-term impact of management strategies and the intersectionality of culture with other demographic factors. This review provides practical recommendations for engineering leaders and identifies areas for future research, aiming to advance the understanding of leadership in multicultural engineering environments.